Clinical Supervision Management Of School Supervisor Tirta Model To Increase Pedagogic Competence Of Junior High School Teacher - Fikron, Fikron; Wahidin, Didin; Warta, Waska; Sudrajat, Adjat (CV. Inara, 2022)
This research is motivated by the weak pedagogic competence of teacher due to the lack of optimal clinical supervision carried out by school supervisors. This study aims to obtain an overview of the planning, organization, implementation, evaluation and barriers to clinical supervision of the TIRTA model of school supervisors to improve the pedagogic competence of junior high school teachers. This research is based on management theory and supervision theory. This study uses a descriptive method with a qualitative approach through interview techniques, observation and documentation in data collection. The results of the study indicate that: (1) Planning has been in accordance with planning theory and programs but has not received maximum support from school principals and infrastructure resources. (2) The organization has been in accordance with the theory of organizing but does not yet have an understanding of their respective duties and responsibilities. (3) The implementation has been in accordance with the implementation theory through socialization, coordination and motivation, but has not been supported by the commitment and competence of teachers. (4) the evaluation has been carried out through an assessment according to the instrument and the results of direct observation, but it has not been maximal in providing solutions to teacher problems. (5) Barriers to the implementation of supervision include professionalism and competence of supervisors, support for understanding and commitment to a quality culture.